Relationship of psychological symptoms, antipsychotics and social data with psychosocial function in schizophrenia patients in Malaysia - A.Talib, Norlelawati; Abdullah, Kartini; Ku Zaifah, Norsidah; Musa, Ramli; Wan Sulaiman, Wan Mohd. Azizi; Abdul Razak, Tariq (Wiley-Blackwell, 2015)
We found that the relationship between psychological symptoms and psychosocial functions were relatively consistent with the findings from the Caucasian population. Additionally, disorganization was the only significant predictor of all dimensions of psychosocial functions. This further emphasized the importance of cognition in psychosocial function. The roles of sulpiride, body mass index and employment status as predictors of psychosocial function were also discussed.